“Walk like a chameleon”: Reflecting on my teaching journey at a South African university - Spencer, Lynda (Educare, 2024)
In 2021, I was asked to give a keynote address at the inaugural symposium of the Swedish national research school, CuEEd-LL – Culturally Empowering Education through Language and Literature, which was to take place in March 2022. I decided to focus my talk on my teaching journey. This paper builds on this keynote and includes my reflections on why and how I teach literature at Rhodes University, a culturally diverse institution. My teaching journey can be described as an unending learning expedition – a journey that has been challenging yet rewarding and continues to enrich me as a Black African female academic in South Africa. In this paper, I draw freely from the elements of a play by dividing my discussion into four parts. I begin with the prologue, which lays out the structure of the paper. Act I is a summary of my teaching journey, where I briefly contextualise higher education in the world, South Africa and Rhodes University before interrogating the role of literature studies in Africa in general and South Africa in particular. Act II contains a discussion of the different theories that inform my teaching philosophy, and the epilogue concludes my teaching journey.